Tualang honey spray versus film spray (Opsite*) as post-long bone fracture fixation wound dressing: a comparative study - Shafei, Surianty; Sharifudin, Mohd Ariff; Ab Rahman, Shafuzain; Sadagatullah, Abdul Nawfar (2014)
Introduction: Tualang honey spray is a new dressing agent with potential wound healing quality and outcome compared to other products. The aim of the study is to compare the advantages of Tualang honey versus spray film (Opsite*) as dressing materials following long bone fracture fixations. This is a preliminary study in Malaysia that involve human as subjects. Methodology: This is a prospective randomized controlled trial involving patients with closed fracture mid-shaft of tibia or femur treated with open reduction and internal fixation (plates or intramedullary devices) at a single tertiary centre. Forty patients fulfilling the criteria of the study were involved. It was a three-arm study that consist of film spray (Opsite*) dressing (n=16), Tualang honey spray (n=13), and control group (n = 11). Each group had a same wound protocol except for the control group that involve only application of non-adhesive film (Mepore). Dressing materials were applied on wounds of the other two groups accordingly, immediately after surgery and on day three following surgery. Wound assessment were done on day 14 and day 42 following surgery. Outcomes evaluated include wound complications and the effects on skin commensals. On the final evaluation on day 42, infection rate and scar formation were also evaluated. Results: A case of superficial surgical site infection was observed from the Opsite* spray group. Acinobacter species was isolated from one of the patients under the control group. There was no association between dressing methods used and wound healing. All wounds healed without any infection at the end of the study. Tualang honey spray was shown to have significant influence in reducing the risk of hypertrophic scar formation and has similar wound outcome as compared to Opsite* spray. Some of the results obtained were comparable to other previous studies on type of dressing and surgical wound healing. Conclusion: Tualang honey spray is a safe alternative for dressing material and was shown comparable to Opsite* spray. Contradict to some of the data available in the literature; its usage is able to promote a good wound healing with a low risk of hypertrophic scar formation.